MODERN APPROACHES TO UPDATING THE PRIMARY EDUCATION CONTENT AND THEIR IMPLEMENTATION DIRECTIONS FOR THE DEVELOPMENT OF JUNIOR SCHOOL STUDENTS’ EMOTIONAL INTELLIGENCE - Kotyk, Tetiana; Shkleda, Lesia (Mountain School of Ukrainian Carpaty, 2022)
The reorientation of the modern Ukrainian school from knowledgeable to competent one is aimed at forming students’ life experience, necessary knowledge, skills and values important for successful implementation in a rapidly changing society. The New Ukrainian school concept proclaims personality-oriented education, i.e. oriented not on the usual mastering of knowledge, but on the formation of the child's personality, his character and attitude to the world. The goal of education system modernization is to transfer the vector of child's external world cognition, created by nature and a man, to mastering the processes of interaction with this world, understanding the meaning of one's own activities. Therefore, the meaningful content of the educational process in primary school becomes particularly relevant in order to implement the New Ukrainian School tasks, especially in the aspect of the development of such student’s personal quality as emotional intelligence. The article reveals the prerequisites for the formation of modern approaches in the educational process organization, the structural components of the work content on the development of the primary school students’ personal worldview, the features of new approaches to the implementation of the primary education content and their personal value orientation and emotional components of education. The results of the analysis of software for the development of younger schoolchildren’s emotional intelligence, presented in current standard educational programs and the State Standard of General Primary Education of Ukraine are highlighted. We have come to the conclusion that the development of emotional intelligence of younger schoolchildren is a cross-cutting content line, i.e. a mandatory educational result which is formed by means of all educational branches and serves as a qualitative changes indicator in the primary education system.